Anti-metastatic Properties of Naproxen-HBTA in a Murine Model of Cutaneous Melanoma - Ercolano, Giuseppe; De Cicco, Paola; Frecentese, Francesco; Saccone, Irene; Corvino, Angela; Giordano, Flavia; Magli, Elisa; Fiorino, Ferdinando; Severino, Beatrice; Calderone, Vincenzo; Citi, Valentina; Cirino, Giuseppe; et al. (Frontiers in Pharmacology, 2019)
The beneficial effects of H2S-release and of COXs-inhibition have been exploited in the design of novel anti-inflammatory drugs, the H2S-releasing non-steroidal anti-inflammatory drugs (H2S-NSAIDs), showing promising potential for chemoprevention in cancers. Here, we evaluated the efficacy of a new H2S-releasing derivative of naproxen, named naproxen-4-hydroxybenzodithioate (naproxen-HBTA), in reducing metastatic melanoma features, both in vitro and in vivo. The novel H2S donor has been prepared following a synthetic scheme that provided high yields and purity. In particular, we investigated the effect of naproxen-HBTA in vitro on several metastatic features of human melanoma cells such as proliferation, migration, invasion and colonies formation and in vivo in a model of cutaneous melanoma. Cell culture studies demonstrated that naproxen-HBTA induced caspase 3-mediated apoptosis and inhibited motility, invasiveness and focus formation. Finally, daily oral treatment with naproxen-HBTA significantly suppressed melanoma growth in mice. In conclusion, by using this dual approach we propose that the COX-2 and H2S pathways could be regarded as novel therapeutic targets/tools to generate new treatment options based on “combination therapy” for melanoma.